(untitled) (Advenimiento, 2021)
Israel’s pre-exilic and exilic period were one of the nation’s most difficult periods. It was marked with spiritual inconsistency which led to moral degeneracy and political instability. During this dark period the king’s role went beyond the political realm. They also played a major role on the spiritual and moral climate of the nation. Saul, David, Solomon and Rehoboam were the only kings with the privilege of reigning over the 12 tribes of Israel. However, Rehoboam not only reigned over the twelve tribes, but since the twelve tribes were divided during his reign; he was also the first to rule over the southern kingdom of Judah. There were twenty kings that reigned in the kingdom of Judah and approximately 70% were young. This paper surveys the twenty kings and analyses selected texts which highlight their age, spiritual status, and the influence they had on the nation. It also answers several questions like why there were young kings, why were some successful, why others failed, and what implications can the church derive from this phenomenon.